2004
DOI: 10.1677/joe.0.1820509
|View full text |Cite
|
Sign up to set email alerts
|

Cloning of somatolactin alpha and beta cDNAs in zebrafish and phylogenetic analysis of two distinct somatolactin subtypes in fish

Abstract: Somatolactin (SL) is a pituitary hormone belonging to the growth hormone/prolactin superfamily, with recognizable homologues in all fish taxa examined to date. Although sequences from most fish share reasonably high sequence identity, several more highly divergent SLs have been reported. Goldfish SL and a second SL protein found in rainbow trout (rtSLP) are remarkably different from each other and also dissimilar to other SLs. It has been unclear whether rtSLP is a recent paralogue restricted to rainbow trout,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 20 publications
6
61
1
Order By: Relevance
“…Therefore, unlike SLR, SL should have existed prior to the FSGD, which produced SLa and SLb paralogs in teleosts. Whereas the presence of SLb hass been reported for some teleost species other than zebrafish (Zhu et al 2004), we could not find SLb in the genomes of medaka and fugu.…”
Section: Resultscontrasting
confidence: 85%
See 1 more Smart Citation
“…Therefore, unlike SLR, SL should have existed prior to the FSGD, which produced SLa and SLb paralogs in teleosts. Whereas the presence of SLb hass been reported for some teleost species other than zebrafish (Zhu et al 2004), we could not find SLb in the genomes of medaka and fugu.…”
Section: Resultscontrasting
confidence: 85%
“…While the duplicated GH seems to have been lost from the genomes of medaka, fugu, or zebrafish, the duplicated SL is retained in zebrafish (Fig. 3) and some other teleost lineages (Zhu et al 2004). The duplicated SLa and SLb have limited sequence similarities (\50%) and the receptor for SLb has not been investigated in any species to date.…”
Section: Ancestral Receptor For Slmentioning
confidence: 99%
“…Interestingly, in the sea bream pituitary gland, PTHrP is found only in the SL-producing cells that would be similar to the recently described SLa cells in zebrafish (Zhu et al, 2004). Indeed, in an earlier study, Ingleton et al (1998) reported that in sea bream, PTHrP and SL are both located in PAS positive cells and that some cells do contain both PTHrP and SL.…”
Section: Pthrp In Teleostssupporting
confidence: 71%
“…The PI consists of corticotropes and melanotropes, which generate -melanocyte stimulating hormone (-MSH) (Liu et al, 2003). As a specific endocrine feature, teleosts share an additional adenohypophyseal cell type: the Somatolactin producing cells, which can be found in the PD of the embryonic and in the PD as well as PI of the adult AH (Zhu et al, 2004, Lopez et al, 2006.…”
Section: Introductionmentioning
confidence: 99%